Bleaching gels containing calcium and fluoride: Effect on enamel erosion susceptibility - Borges, Alessandra B. [UNESP]; Torres, Carlos R. G. [UNESP]; De Souza, Paulo A. B. [UNESP]; Caneppele, Taciana M. F. [UNESP]; Santos, Luciana F. T. F. [UNESP]; Magalhães, Ana Carolina (Hindawi, 2012)
This in vitro study evaluated the effect of 35 hydrogen peroxide (HP) bleaching gel modified or not by the addition of calcium and fluoride on enamel susceptibility to erosion. Bovine enamel samples (3 mm in diameter) were divided into four groups (n = 15) according to the bleaching agent: control-without bleaching (C); 35 hydrogen peroxide (HP); 35 HP with the addition of 2 calcium gluconate (HP + Ca); 35 HP with the addition of 0.6 sodium fluoride (HP + F). The bleaching gels were applied on the enamel surface for 40 min, and the specimens were subjected to erosive challenge with Sprite Zero and remineralization with artificial saliva for 5 days. Enamel wear was assessed using profilometry. The data were analyzed by ANOVA/ Tukey's test (P 0.05). There were significant differences among the groups (P = 0.009). The most enamel wear was seen for C (3.37 ± 0.80 μm), followed by HP (2.89 ± 0.98 μm) and HP + F (2.72 ± 0.64 μm). HP + Ca (2.31 ± 0.92 μm) was the only group able to significantly reduce enamel erosion compared to C. The application of HP bleaching agent did not increase the enamel susceptibility to erosion. However, the addition of calcium gluconate to the HP gel resulted in reduced susceptibility of the enamel to erosion. © 2012 Alessandra B. Borges et al.